The conjunctival microbiome before and after azithromycin mass drug administration for trachoma control in a cohort of Tanzanian children - Pickering, Harry; Ramadhani, Athumani M.; Massae, Patrick; Mafuru, Elias; Malisa, Aiweda; Mbuya, Kelvin; Makupa, William; Mtuy, Tara; Derrick, Tamsyn; Houghton, Joanna; Bailey, Robin L.; Mabey, David C. W.; et al. (Frontiers in Public Health, 2022)
Background Trachoma, caused by ocular infection with Chlamydia trachomatis, is a neglected tropical disease that can lead to blinding pathology. Current trachoma control programmes have successfully used mass drug administration (MDA) with azithromycin to clear C. trachomatis infection and reduce transmission, alongside promoting facial cleanliness for better personal hygiene and environmental improvement. In areas of low-trachoma endemicity, the relationship between C. trachomatis infection and trachomatous disease weakens, and non-chlamydial bacteria have been associated with disease signs. Methods We enrolled a cohort of children aged 6–10 years from three adjacent trachoma endemic villages in Kilimanjaro and Arusha regions, Northern Tanzania. Children were divided into four clinical groups based on the presence or absence of ocular C. trachomatis infection and clinical signs of trachomatous papillary inflammation (TP). To determine the impact of treatment on the ocular microbiome in these clinical groups, we performed V4-16S rRNA sequencing of conjunctival DNA from children 3–9 months pre-MDA (n = 269) and 3 months post-MDA (n = 79). Results Chlamydia trachomatis PCR-negative, no TP children had the highest pre-MDA ocular microbiome alpha diversity, which was reduced in C. trachomatis infected children and further decreased in those with TP. Pre-MDA, Haemophilus and Staphylococcus were associated with C. trachomatis infection with and without concurrent TP, while Helicobacter was increased in those with TP in the absence of current C. trachomatis infection. Post-MDA, none of the studied children had ocular C. trachomatis infection or TP. MDA increased ocular microbiome diversity in all clinical groups, the change was of greater magnitude in children with pre-MDA TP. MDA effectively reduced the prevalence of disease causing pathogenic non-chlamydial bacteria, and promoted restoration of a normal, healthy conjunctival microbiome. Conclusion We identified Helicobacter as a non-chlamydial bacterium associated with the clinical signs of TP. Further investigation to determine its relevance in other low-endemicity communities is required. MDA was shown to be effective at clearing C. trachomatis infection and other non-chlamydial ocular pathogens, without any detrimental longitudinal effects on the ocular microbiome. These findings suggest that azithromycin MDA may be valuable in trachoma control even in populations where the relationship between clinical signs of trachoma and the prevalence of current ocular C. trachomatis infection has become dissociated.